Evaluation of Carcinogenic and Non-Carcinogenic Risk of Heavy Metals Due to the Consumption of Vegetables Produced in the Greenhouse of Markazi Province - Kourosh Mokhtari; Hossein Mazaheri; Amir Hossein Baghaie; Ali Hassani Joshaghani (Shiraz University of Medical Sciences, 2019)
Background: High concentration of heavy metals and NO 3 in vegetables may pose serious health risks to humans. Therefore, this research was done to evaluate the carcinogenic and non- carcinogenic risk of heavy metals and NO 3 due to the consumption of most important greenhouse vegetables produced in Markazi province. Methods: In this descriptive study, sampling of cucumber, tomato, and bell pepper produced in the greenhouses of Markazi province was done randomly and the concentration of Pb, Cd, Cu, Ni and NO 3 of them were determined. Non-cancer risk related to heavy metals and NO 3 sorption from vegetables was evaluated using the EPA method for men and women. Results: The mean concentration of all the studied metals except Cu was in the allowable concentration range. The mean concentration of NO 3 in the cucumber was 300 mg/kg FW, which was about 1.5 times higher than the maximum allowable concentration of that in vegetables. The HQ of Pb, Cd, Ni, Cu and NO 3 for all population groups were smaller than 1. The results showed that NO 3 and Pb were the major risk contributor for the consumers. The excess lifetime cancer risks of Ni for all receptor groups were greater than 1×10 −6 . Conclusion: The results of this study showed that the total risk index of heavy metals and NO 3 through consumption of greenhouse vegetables grown in Markazi province was below one. Also, in the most age groups this index is greater for women related to the men.